(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Probability distribution is important to those who are interested in the subject of mathematical statistics, so in this research a probability function of the mixed distribution Frechet-Frechet was formed and its parameters were estimated using maximum likelihood and moment methods. These methods are applied on real data which represents the number of cancer cases in Iraq for the years (1991-2016).